Kinerja Karyawan melalui Pengalaman Kerja dan Motivasi Kantor Cabang BRI Bangkalan Madura dengan Manajemen Pengetahuan Sebagai Variabel Intervening - Dewiati, Arinda; Wildan, Muhammad Alkirom (Management Department of Economics and Business Of Trunojoyo Madura University, 2024)
This research aims to determine the effect of work experience and motivation on the performance of bri branch office employees in bangkalan madura district by using a knowledge management approach as an intervening variable. The method used in this research is a quantitative method, namely data is the form of numbers and analysis uses statistics with a sample zize of 96 people. Data collection methods using questionnaires and analyzing the data using multiple linear regression and path analysis. The result of this research show that work experience partially has positive and significant effect on knowledge management with a significant value of 0.000 0.05, motivation also has partially has a significant positive effect on knowledge management with a significant value of 0.000 0.05, knowledge management also has a positive effect and significant value of 0.009 0.05, work experience also partially has significant positive effect on employee performance with a significant value of 0,009 0,05. Work experience also partialy has a significant positive effect on employe performance with a significant value of 0,000 0,05 and motivation also partially has a significant positive effect on knowledge management with a significant value of 0,000 0,05.